Submerged arc welding of Ramor 500 Steel and numerical modeling of the residual stress - Gur, Ali Kaya; Ozay, Cetin; Taskaya, Semih (Walter de Gruyter Gmbh, 2020)
Ramor 500 armor steel is classified as a high-strength ballistic protection steel with thicknesses of 505-590 HV with a thickness of 2-30 mm. ANSYS is a simulation software program used in engineering fields. This program is used after the modeling phase and allows testing in a virtual environment before the prototype is produced. In this study, 3 mm thick and 65 x 55 mm Ramor 500 steel which is used as armor steel and basic combat vehicle in the armed forces in the market has been selected. These pairs of steel groups were combined by submerged arc welding at 250 constant amps, 20, 25, 30 volt voltages and 20, 25, 30 cm x min welding feed rates. Radiographic examination tests, metallographic microstructure and microhardness investigations of the structures formed in the intersection after the joints were performed. ANSYS package software has analyzed the mechanical distortions that occur after the merge process. As a result of the analysis, it was examined that all weldings had full penetration in radiographic examination test. In the microstructure examination, a coarse-grained structure from the weld seam to the base material and a grain structure that changed from the smaller grained structure were observed. In the microhardness test and ANSYS software, it was observed that the hardness of the welded seams increased compared to the hardness of the base material, elastic tensions were very high during the welding process and it was replaced by permanent stresses.
Keywords: Ramor 500; submerged arc welding; ANSYS; mechanical stress